Detection of Angiotensin II type I‐receptor antibodies in transplant glomerulopathy. Issue 11 (22nd November 2018) - Bussolino, Stefania; Dolla, Caterina; Ariaudo, Claudia; Civiletti, Federica; Messina, Maria; Mella, Alberto; Caorsi, Cristiana; Amoroso, Antonio; Barreca, Antonella; Papotti, Mauro; Giunti, Sara; Fop, Fabrizio; et al.
Abstract: Background: Transplant glomerulopathy (TG) is an important cause of late graft loss. The role of angiotensin type 1‐receptor antibodies (AT1 R‐Ab) in TG is not known. Methods: All the TG cases (N = 137) between January 2007 and December 2014 (N = 1410) were analyzed. Donor‐specific anti‐HLA antibodies (DSA) at the time of biopsy and AT1 R‐Ab IgG (positive, >17 UI/mL; "at risk, " 10‐17 UI/mL; negative, <10 UI/mL) in pre‐transplant sera (PT‐Ab) and at biopsy time (BT‐Ab) were studied. Results: AT1 R‐PT‐Ab + and AT1 R‐BT‐Ab + patients were 16.5% (51.5% "at risk") and 11.5% (27.4% "at risk"), respectively. Clinical correlations were found between AT1 R‐Ab and HCV infection, number of transplants, and age. Considering Banff scores, ptc was higher in DSA + patients vs AT1 R‐PT‐Ab + ( P  = 0.002) or AT1 R‐BT‐Ab + ( P  = 0.001) without differences in g and chronicity score (ci + ct); cg showed lower scores in DSA + patients vs AT1 R‐BT‐Ab + ( P  = 0.001). Graft survival was not influenced by the presence of AT1 R‐Ab, AT1‐R‐Ab titer or MFI, but we observed a longer graft survival in patients with both AT1 R‐BT‐Ab + or "at risk" and DSA + vs patients positive only for DSA ( P  = 0.02), for AT1 R‐BT‐Ab ( P  = 0.019) or AT1 R‐BT‐Ab "at risk" ( P  = 0.039). Conclusion: AT1 R‐Ab showed no independent prognostic role in TG in this pilot analysis.